FINANCIAL PERFORMANCE MEMODERASI HUBUNGAN AGENCY COST DAN DIVIDEND POLICY - Zenabia, Tsarina; Effriyanti (Publika Citra Media, 2024)
Dividend distribution is still the main attraction for investors compared to capital gains because dividends promise a more certain thing and dividend distribution aims to maximize shareholder prosperity. This study examines the effect of agency costs on dividend policy with financial performance as moderation in the non-cyclical manufacturing industry. Quantitative research method with secondary data obtained from the Indonesia Stock Exchange (IDX) for the period 2018-2022. Partial test results of executive compensation and free cash flow have a positive effect on dividend policy with prob. value 0.0014 < α 0.05 and 0.0027 < α 0.05. Return on equity (ROE) successfully moderates the negative effect of common stock distribution and dividend policy with prob. value 0.0153 < α 0.05. Similarly, ROE strengthens the positive relationship of free cash flow on dividend policy with prob. value 0.0004 < α 0.05 with an initial coefficient of 1.0968 before moderation to 4.4727 after moderation.